Considerations on the implementation of DCT: a SCAT-based analysis of fact-finding interviews in Europe and the United States, with implications for regions newly adopting DCT, including Japan - Taruno, Hiroyuki; Ikeda, Koji; Oikawa, Marika; Sato, Takahiro; Suzuki, Yuka; Shikano, Mayumi (Frontiers in Medicine, 2025)
IntroductionDecentralized clinical trials (DCT) are becoming more common. In regions where DCT will be widely adopted, including Japan, issues in implementing DCT must be identified and addressed.Materials and methodsIn this study, we interviewed the clinical development staff at pharmaceutical and medical device companies, or clinical research organizations in Europe and the United States and then analyzed their information to understand the transition to and current status of DCT from a practical perspective. Steps for Coding and Theorization qualitative data analysis was used.ResultsDCT, along with the rapid digitisation of medical care, occurred in some institutions because of the novel coronavirus disease pandemic. Our results confirmed that introducing DCT allowed patients who would otherwise have struggled to participate in traditional trial formats to have easier access to clinical trials, allowing them to experience new treatments and reducing the inconvenience of travel burdens and waiting times for patients who previously had to travel long distances to medical institutions to participate in clinical trials. However, introducing new DCT can be challenging for several reasons, including local culture, regulations regarding home and telemedicine, online sharing of medical record information with trial personnel, the development of Internet of Things infrastructure, information technology literacy of trial personnel and subjects, and the associated costs.DiscussionWe identified specific issues common to medical devices and pharmaceutical clinical trials. In addition, the experiences of those in charge were used to identify specific issues in the DCT introduction phase. Information on the latest overseas DCT methods, such as patient neighborhood institutions and remote services that use ambulances, mobile vans, tents, supermarkets, and pharmacies to replace implementing medical institutions, was obtained. Currently, Japan lags behind Europe and the United States in terms of DCT diffusion. However, we hope to resolve many of the aforementioned issues in the future to actively introduce DCT in Japan, thereby preventing Japan from being left behind in international joint trials. Furthermore, this study’s findings will be of significant value to countries and regions that are striving to fully adopt DCT.